MENINGKATKAN KOMPETENSI PEDAGOGI GURU MELALUI LESSON STUDY MENUJU MUTU PEMBELAJARAN GURU - Syafruddin, Syafruddin (UNIVERSITAS MUHAMMADIYAH METRO, 2015)
This article aims to examine strategies for improving pedagogical competence through in service training that is more focused on the empowerment of teachers in accordance with the capacity and the problems faced by teachers in the classroom, to improve the quality of teacher learning through lesson study. lesson study is a model of professional development of educators through collaborative learning and continuous assessment based on collegiality and mutual learning. to build a learning community. lesson study selected and implemented in order to improve the pedagogical competence as an effective way to improve the quality of learning and teaching in class. Lesson study carried out in the form of a cycle plan-do-see. through lesson study expected to increase pedagogical competence and increase the quality of learning.